PERANCANGAN DAN IMPLEMENTASI ABSENSI ELEKTRONIK BERBASIS RFID UNTUK APARATUR KELURAHAN NEGLASARI - Haris Usman; Salim Maula Amrullah; Abdur Rosyid Amrullah; Andrianto; Danang Ardiansyah; Intra Sepriansa; Manzis Ilham Maulana; Muhamad Hariri Fadilah; Rivaldi Pratama Kurnia; Salsa Nabila; Intan Kumalasari (Abdi Jurnal Publikasi, 2025)
The manual attendance system still in use often creates various problems, such as delayed recording, inaccurate attendance data, and the potential for manipulation. These issues hinder the optimal monitoring of discipline among officials in Neglasari Urban Village. This community service activity aims to design and implement an RFID-based electronic attendance system as a faster, more effective, and more accurate alternative. The implementation process included identifying user needs, designing the hardware and software, installing the device, conducting system trials, and carrying out evaluations with the village officials. The results indicate that the RFID system is capable of accelerating the attendance recording process, providing more accurate data, and generating easily accessible automatic recaps. Users also reported that this system is more efficient than the previous method. Therefore, the implementation of RFID has proven to support improved discipline and transparency in managing attendance records for village officials.